Segmenting, Targeting, and Positioning Analysis of Outpatient Revisits - Soffiyani, Nisa (Riwayat: Educational Journal of History and Humanities, 2025)
Increasing outpatient repeat visits is one of the main indicators of service success in healthcare facilities. This study aims to analyze the implementation of segmenting, targeting, and positioning (STP) strategies to support the increase in outpatient repeat visits through a systematic review of ten national and international journals. The method used was a systematic literature review based on literature reviewed from 20172025 with inclusion criteria for studies discussing STP in outpatient services, particularly those focusing on the determinants of repeat visits. The analysis is based on a descriptive and comparative approach to segmentation variables (demographics, geography, psychographics, behavior), target determination (patients with curative needs, insurance access, specific domiciles), and service positioning strategies. The review results show that precise and data-driven segmentation allows mapping the characteristics of loyal patients, while effective targeting improves promotion and service efficiency. Prominent positioning on service quality, ease of access, and digital innovation has been shown to strengthen brand image and patient trust. The dominant factors influencing repeat visit decisions are service satisfaction, perceived quality, and ease of facility access. The study's conclusion confirms that an integrated STP strategy can significantly increase outpatient repeat visits. Recommendations are directed at optimizing patient information systems, marketing collaboration, and strengthening the image of services based on specific patient needs.